Analysis of the antibody titre in sows vaccinated against classical swine fever at four gestation ages - Noboa, Jacqueline (2019)
The immune response acquired by vaccination against classical swine fever (CSF) in sows at four gestational ages (70, 75, 80 and 90 days) was evaluated using the Pest-Vac® vaccine (Pfizer). Blood samples were taken 24 hours before vaccination and 72 hours after parturition. The level of antibodies was determined by a blocking ELISA. No significant difference was found between the antibody titres generated by the vaccination according to gestational age nor between the pre-vaccination and post-partum samples. However, the effect of the number of parturitions, used as a covariate, presented a significant difference (p<0.05) in the percentage of blocking of antibodies against PPC.